Social and Psychological Training as a Method of Develop¬ment of Public Servants’ Communicative Competence - Solovey, O. (Psychological Prospects Journal, 2013)
The article deals with the communicative competence as a part of life and professional success of a public service specialist. The approaches to the definition of the communicative competence and characteristics that influence the effective communication are examined. The analysis of peculiarities of social and psychological training introduction as an active method of communicative competence development is realized.